A negative electrode sheet, a method for manufacturing the same, and an application thereof

CN118969961BActive Publication Date: 2026-10-27XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411038827.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2026-10-27
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

但是当合金类负极占比变大(例如,5-50wt%)时,硬碳负极提供的缓冲空间不足时,极片膨胀,经过几次充放电后,材料会发生粉化,与电解液发生副反应,容量迅速衰减

Benefits of technology

[0040]在集流体至少一个表面上依次叠层设置多个第一复合材料层和第二复合材料层,所有第一复合材料层的材料均包括第一碳材料、合金类负极材料和第一导电剂,位于集流体同一表面上的多个第一复合材料层的材料中合金类负极材料、第一导电剂的质量含量均自靠近集流体一侧至远离集流体一侧依次减小,提高了靠近集流体一侧负极片内钠离子等的迁移速度,缩小远离集流体一侧和靠近集流体一侧合金类负极材料的嵌钠程度的差异(也即优化了负极极片远离集流体一侧和靠近集流体一侧合金类负极材料的嵌钠深度),缓解远离集流体一侧合金类负极材料由于嵌钠深度过大而导致的极片粉碎问题,保证负极极片的稳定性;此外,表层再设置一层含有第二碳材料的第二复合材料层,可束缚负极极片的膨胀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118969961B_ABST
    Figure CN118969961B_ABST
Patent Text Reader

Abstract

The application provides a negative electrode sheet, a preparation method and application thereof. The negative electrode sheet comprises a current collector, at least one surface of the current collector is sequentially provided with at least two layers of first composite material layers and second composite material layers; the material of all the first composite material layers comprises a first carbon material, an alloy type negative electrode material and a first conductive agent; in the material of any two adjacent first composite material layers, the mass content of the alloy type negative electrode material in the material of the first composite material layer close to the current collector is greater than the mass content of the alloy type negative electrode material in the material of the first composite material layer close to the second composite material layer; and the material of the second composite material layer comprises a second carbon material and a second conductive agent. The negative electrode sheet can solve the problem of large negative electrode expansion of a mixed negative electrode of a hard carbon and an alloy type negative electrode material after sodium insertion in a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery technology, and in particular to a negative electrode sheet, its preparation method and application. Background Technology

[0002] With the increasing global demand for clean energy, sodium-ion batteries, as a novel battery technology, have attracted widespread attention due to their advantages such as abundant resources, low cost, and high safety. Alloy-type anodes are a crucial component of sodium-ion batteries. Compared to commonly used soft carbon and hard carbon anodes, alloy-type anodes offer ultra-high capacity, significantly improving the energy density of sodium-ion batteries and representing the future direction of sodium-ion battery technology development. However, alloy-type anodes suffer from severe volume expansion during charge and discharge, leading to electrode material pulverization, accelerated reaction with the electrolyte, loss of active sodium, and increased impedance, thereby reducing battery performance.

[0003] To address the aforementioned issues, the main technology involves mixing an alloy-type negative electrode with hard carbon and then uniformly coating it onto an aluminum foil substrate. This method only mitigates the expansion problem of the alloy-type negative electrode when its proportion is small (e.g., 0.5-2 wt%). The hard carbon material, with its minimal expansion, provides a buffer space for the alloy-type negative electrode, ensuring structural stability and improving battery cycle life. However, when the proportion of the alloy-type negative electrode increases (e.g., 5-50 wt%), the buffer space provided by the hard carbon negative electrode becomes insufficient, leading to electrode expansion. After several charge-discharge cycles, the material pulverizes, undergoes side reactions with the electrolyte, and experiences rapid capacity decay. Summary of the Invention

[0004] In view of this, one objective of this application is to provide a negative electrode sheet, wherein multiple first composite material layers and second composite material layers are sequentially stacked on at least one surface of a current collector. The materials of all the first composite material layers include a first carbon material, an alloy-type negative electrode material, and a first conductive agent. In the materials of the multiple first composite material layers located on the same surface of the current collector, the mass content of the alloy-type negative electrode material and the first conductive agent decreases sequentially from the side closer to the current collector to the side farther away from the current collector. This increases the migration speed of sodium ions, etc., in the negative electrode sheet near the current collector, reduces the difference in the degree of sodium embedding of the alloy-type negative electrode material on the side farther away from the current collector and the side closer to the current collector (that is, optimizes the sodium embedding depth of the alloy-type negative electrode material on the side farther away from the current collector and the side closer to the current collector), alleviates the electrode sheet crushing problem caused by excessive sodium embedding depth of the alloy-type negative electrode material on the side farther away from the current collector, and ensures the stability of the negative electrode sheet. In addition, a second composite material layer containing a second carbon material is set on the surface to restrain the expansion of the negative electrode sheet.

[0005] Another objective of this application is to provide a method for preparing a negative electrode sheet.

[0006] Another object of this application is to provide a secondary battery.

[0007] To achieve the above objectives, the first aspect of this application proposes a negative electrode sheet, including a current collector, wherein at least two layers of a first composite material and a second composite material are sequentially stacked on at least one surface of the current collector.

[0008] All the materials of the first composite material layer include a first carbon material, an alloy-type negative electrode material, and a first conductive agent; among the materials of any two adjacent first composite material layers located on the same surface of the current collector, the mass content of the alloy-type negative electrode material in the material of the first composite material layer closer to the current collector is greater than the mass content of the alloy-type negative electrode material in the material of the first composite material layer closer to the second composite material layer, and the mass content of the first conductive agent in the material of the first composite material layer closer to the current collector is greater than the mass content of the first conductive agent in the material of the first composite material layer closer to the second composite material layer.

[0009] The materials of the second composite material layer include a second carbon material and a second conductive agent.

[0010] In some embodiments, both the first carbon material and the second carbon material include at least one of hard carbon and soft carbon;

[0011] And / or, the alloy-type negative electrode material includes at least one of antimony, tin, phosphorus, silicon, bismuth, and germanium;

[0012] And / or, the first conductive agent and the second conductive agent include at least one of conductive carbon black, superconducting carbon, conductive graphite, carbon nanotubes, and graphene.

[0013] In some embodiments, the total mass content of the alloy-type negative electrode material in the negative electrode sheet is greater than 0% and less than 49.5%.

[0014] In some embodiments, the mass content of the first carbon material in the first composite material layer is greater than or equal to the mass content of the alloy-type anode material.

[0015] In some embodiments, the mass content of the first carbon material in the first composite material layer is less than or equal to the mass content of the second carbon material in the second composite material layer.

[0016] In some embodiments, the mass content of the first conductive agent in the material of the first composite material layer is 0.4-5.0%.

[0017] In some embodiments, the mass content of the second conductive agent in the material of the second composite layer is 0.5-5.0%.

[0018] In some embodiments, the mass content of the first carbon material in the first composite material layer is 49.5-99%.

[0019] In some embodiments, when the first composite material layer has two layers, the mass content of the alloy-type negative electrode material in the first composite material layer is m, where 0 < m ≦ 49.5%.

[0020] In other embodiments, when the number of layers in the first composite material layer is greater than two, the mass content of the alloy-type negative electrode material in the first composite material layer is n, where 0 ≤ n ≤ 49.5%.

[0021] In some embodiments, the second carbon material has a mass content of 90-99% in the second composite material layer.

[0022] In some embodiments, all the materials of the first composite material layers also include a first adhesive.

[0023] In some embodiments, the material of the second composite layer further includes a second adhesive.

[0024] In some embodiments, the mass content of the first adhesive in the material of the first composite layer is 0.5-5.0%.

[0025] In some embodiments, the mass content of the second adhesive in the material of the second composite layer is 0.5-5.0%.

[0026] In some embodiments, both the first adhesive and the second adhesive comprise at least one of styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.

[0027] In some embodiments, the number of first composite material layers on the same surface of the current collector is two, and the mass content of the alloy-type negative electrode material and the first conductive agent in the material of the first composite material layer adjacent to the current collector is a% and b% respectively; the mass content of the alloy-type negative electrode material and the first conductive agent in the material of the first composite material layer adjacent to the second composite material layer is c% and d% respectively; wherein c, d, a, and b satisfy:

[0028] 20% ≤ c / (a+c) < 50%, and / or 20% ≤ d / (b+d) < 50%.

[0029] In some embodiments, the at least two layers of the first composite material and the second composite material are stacked sequentially on both opposite surfaces of the current collector.

[0030] In some embodiments, the total thickness of all the first composite material layers located on the same surface of the current collector is 60-90 μm.

[0031] In some embodiments, the total number of the first composite material layer located on the same surface of the current collector is 2-5 layers.

[0032] In some embodiments, the thickness of the second composite material layer located on the same surface as the current collector is 1-5 μm.

[0033] In some embodiments, the double-sided thickness of the negative electrode sheet is 130-210 μm (including the thickness of the current collector, the thickness of the first composite material layer and the thickness of the second composite material layer on all surfaces of the current collector).

[0034] In some embodiments, the ratio of the areal density of the first composite material layer to the areal density of the second composite material layer is (9-9.9):(0.1-1).

[0035] The second aspect of this application discloses a method for preparing a negative electrode sheet, comprising:

[0036] Prepare the first composite material layer slurry and the second composite material layer slurry respectively;

[0037] Using the first composite material layer slurry and the second composite material layer slurry as raw materials, the first composite material layer and the second composite material layer are sequentially formed on at least one surface of the current collector by a layered coating method.

[0038] A third aspect of this application provides a secondary battery, comprising a positive electrode, a separator, and a negative electrode, wherein the negative electrode is the negative electrode described in this application.

[0039] The negative electrode sheet described in this application can bring at least the following technical effects:

[0040] Multiple first composite material layers and second composite material layers are sequentially stacked on at least one surface of the current collector. The materials of all first composite material layers include a first carbon material, an alloy-type negative electrode material, and a first conductive agent. The mass content of the alloy-type negative electrode material and the first conductive agent in the materials of the multiple first composite material layers located on the same surface of the current collector decreases sequentially from the side closer to the current collector to the side farther away from the current collector. This increases the migration speed of sodium ions and other substances in the negative electrode sheet near the current collector and reduces the difference in the degree of sodium embedding of the alloy-type negative electrode material on the side farther away from the current collector and the side closer to the current collector (that is, it optimizes the sodium embedding depth of the alloy-type negative electrode material on the side farther away from the current collector and the side closer to the current collector). This alleviates the problem of electrode sheet shattering caused by excessive sodium embedding depth of the alloy-type negative electrode material on the side farther away from the current collector and ensures the stability of the negative electrode sheet. In addition, a second composite material layer containing a second carbon material is set on the surface to restrain the expansion of the negative electrode sheet.

[0041] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0042] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings.

[0043] in:

[0044] Figure 1 This is a schematic diagram of the structure of a negative electrode sheet, which is an exemplary embodiment of this application.

[0045] Figure 2 This is a schematic diagram of the structure of a negative electrode sheet, which is shown as another exemplary embodiment of this application.

[0046] Figure label:

[0047] 1-Current collector; 101-First surface; 102-Second surface; 2-First composite material layer; 201-First composite material layer A; 202-First composite material layer B; 3-Second composite material layer. Detailed Implementation

[0048] The embodiments of this application are described in detail below, with examples of these embodiments illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0049] In this application, the disclosure of numerical ranges includes all values ​​throughout the range and the disclosure of further subdivisions of the range, including the endpoints and subranges given for these ranges.

[0050] Unless otherwise specified, all raw materials and equipment involved in this application are self-made through commercial means or known methods; and all methods involved are conventional methods unless otherwise specified.

[0051] The inventors discovered that in related technologies, when alloy-type negative electrodes are mixed with hard carbon, and the proportion of alloy-type negative electrode material is large, the buffer space provided by hard carbon and other carbon materials is insufficient, causing the electrode to expand. After several charge-discharge cycles, the material will pulverize and undergo side reactions with the electrolyte, resulting in rapid capacity decay.

[0052] Based on the above findings, the inventors further discovered that by improving the structure of the negative electrode, they could address the expansion problem of alloy-type negative electrodes in sodium-ion batteries. From a battery kinetics perspective, as sodium ions migrate within the negative electrode, the greater the migration depth, the more difficult the migration becomes, and the amount of migrating sodium ions gradually decreases. Therefore, in the negative electrode, the degree of sodium embedding on the side farther from the current collector is higher than that on the side closer to the current collector, resulting in greater expansion on the side farther from the current collector and faster pulverization on the side farther from the current collector. In contrast, conventional negative electrode sheets have uniform coating, with the material composition being consistent on both sides, resulting in homogeneous coating. When the expansion of the negative electrode material used is significant, the problems with this coating scheme become more pronounced.

[0053] The inventors further discovered that by sequentially stacking multiple first composite material layers and second composite material layers on the current collector, all the materials in the first composite material layers include a first carbon material, an alloy-type negative electrode material, and a first conductive agent. The mass content of the alloy-type negative electrode material and the first conductive agent in the materials of the multiple first composite material layers decreases sequentially from the side closer to the current collector to the side farther away from the current collector. This can increase the migration speed of sodium ions and other particles within the negative electrode sheet near the current collector, reduce the difference in sodium embedding depth between the sides of the alloy-type negative electrode material near and far from the current collector (i.e., optimize the sodium embedding depth of the alloy-type negative electrode material near and far from the current collector), alleviate the electrode sheet shattering problem caused by excessive sodium embedding depth on the side of the alloy-type negative electrode material far from the current collector, and thus ensure the stability of the negative electrode sheet. Furthermore, by adding a second composite material layer containing a second carbon material on the surface, the expansion of the negative electrode sheet can be restrained.

[0054] <Negative electrode sheet>

[0055] A negative electrode sheet according to an embodiment of this application is described below with reference to the accompanying drawings.

[0056] Figure 1 This is a schematic diagram of the structure of a negative electrode sheet, which is an exemplary embodiment of this application.

[0057] like Figure 1As shown, the negative electrode sheet of this embodiment includes a current collector 1, and at least two layers of first composite material 2 and second composite material 3 are sequentially stacked on at least one surface of the current collector 1. Wherein,

[0058] All materials in the first composite material layer 2 include a first carbon material, an alloy-type negative electrode material, and a first conductive agent. Among any two adjacent first composite material layers on the same surface of the current collector, the mass content of the alloy-type negative electrode material in the first composite material layer closer to the current collector is greater than that in the first composite material layer closer to the second composite material layer. Similarly, among any two adjacent first composite material layers, the mass content of the first conductive agent in the first composite material layer closer to the current collector is greater than that in the first composite material layer closer to the second composite material layer. This configuration increases the migration rate of sodium ions and other particles within the negative electrode sheet near the current collector, reduces the difference in sodium embedding degree between the alloy-type negative electrode material near and away from the current collector, alleviates the fragmentation of the alloy-type negative electrode material far from the current collector, and ensures the stability of the negative electrode sheet.

[0059] The second composite material layer 3 comprises a second carbon material and a second conductive agent, which can restrain the expansion of the negative electrode sheet.

[0060] In some embodiments, the first carbon material and the second carbon material are both including, but not limited to, at least one of hard carbon, soft carbon, etc.

[0061] It should be noted that in the embodiments of this application, the first carbon material and the second carbon material can be the same or different, but preferably the same.

[0062] As a preferred example, the negative electrode is a sodium-ion battery negative electrode, and both the first carbon material and the second carbon material are hard carbon.

[0063] For example, the hard carbon in the embodiments of this application includes, but is not limited to, at least one of polymer-derived hard carbon materials, fossil fuel-derived hard carbon materials, and biomass-derived hard carbon materials.

[0064] In some embodiments, the alloy-type negative electrode material includes, but is not limited to, at least one of antimony, tin, phosphorus, silicon, bismuth, germanium, etc.

[0065] In some embodiments, the first conductive agent and the second conductive agent include, but are not limited to, at least one of conductive carbon black (SP), superconducting carbon, conductive graphite, carbon nanotubes, graphene, etc.

[0066] It should be noted that the first carbon material in each first composite material layer can be the same or different, preferably the same; the alloy anode material in each first composite material layer can be the same or different, preferably the same; the first conductive agent in each first composite material layer can be the same or different, preferably the same; the first conductive agent and the second conductive agent can be the same or different, preferably the same.

[0067] In some embodiments, the total mass content of alloy-type negative electrode material in the negative electrode sheet is greater than 0% and less than 49.5%, including but not limited to 0.1%, 5%, 10%, 20%, 30%, 40% or 49.5%.

[0068] In some embodiments, the mass content of the first carbon material in the first composite material layer 2 is greater than or equal to the mass content of the alloy-type anode material.

[0069] In some embodiments, the mass content of the first carbon material in the first composite material layer 2 is 49.5-99%, including but not limited to 49.5%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 99%.

[0070] In some embodiments, when the first composite material layer has two layers, the mass content of the alloy-type negative electrode material in the first composite material layer is m, where 0 < m ≤ 49.5%. For example, the value of m includes, but is not limited to, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 49.5%.

[0071] In other embodiments, when the number of layers in the first composite material layer 2 is greater than two, the mass content of the alloy-type negative electrode material in the first composite material layer 2 is n, where 0 ≤ n ≤ 49.5%. For example, the value of n includes, but is not limited to, 0%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 49.5%. In the embodiments of this application, the mass content of the alloy-type negative electrode material in the first composite material layer is within the above range, which ensures that the negative electrode remains flat after multiple charge-discharge cycles, and the active material and current collector are firmly bonded. If the mass content is higher than 49.5%, electrode wrinkling and surface cracking are likely to occur during cycling; simultaneously, the electrolyte enters the electrode interior through the cracks and reacts directly with the internal active material, further accelerating the expansion and pulverization of the active material.

[0072] In some embodiments, the mass content of the first conductive agent in the material of the first composite layer 2 is 0.4-5.0%, including but not limited to 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0073] In some embodiments, the mass content of the first carbon material in the first composite material layer 2 is less than or equal to the mass content of the second carbon material in the second composite material layer 3. This arrangement aims to increase the content of the conductive agent in the composite material layer near the current collector, which facilitates the diffusion of electrons from the current collector to the surface of each active material through the conductive agent. This promotes the insertion of sodium ions into the active materials, balances the sodium insertion depth of the active materials near and away from the current collector, alleviates the sodium insertion depth of the surface active materials, and mitigates problems such as expansion and pulverization.

[0074] In some embodiments, the mass content of the second carbon material in the second composite material layer 3 is 90-99%, including but not limited to 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or 99%.

[0075] In some embodiments, the mass content of the second conductive agent in the material of the second composite layer 3 is 0.5-5.0%, including but not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0076] In some embodiments, all the materials of the first composite material layer 2 also include a first adhesive.

[0077] In some embodiments, the material of the second composite layer 3 further includes a second adhesive.

[0078] In some embodiments, the mass content of the first adhesive in the material of the first composite layer 2 is 0.5-5.0%, including but not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0079] In some embodiments, the mass content of the second adhesive in the material of the second composite layer is 0.5-5.0%, including but not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0080] In some embodiments, the first adhesive and the second adhesive include, but are not limited to, at least one of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), sodium alginate (SA), polyvinylidene fluoride (PVDF), etc.

[0081] It should be noted that styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are broadly considered adhesives, but if we further subdivide them, SBR is an adhesive and CMC is a thickener.

[0082] As an optional example, the mass of each first composite material layer located on the same surface of the current collector is equal, and the ratio of the total mass of all the materials of the first composite material layers to the mass of the second composite material layer is (9-9.9):(0.1-1), including but not limited to 9.9:0.1, 9.7:0.3, 9.5:0.5, 9.3:0.7, or 9.1:0.9 or 9.0:1.0, etc.

[0083] As another alternative example, the masses of the materials of each first composite material layer located on the same surface of the current collector are not equal and gradually decrease from the side closer to the current collector to the side farther away from the current collector; the ratio of the total mass of the materials of all first composite material layers to the mass of the second composite material layer is (9-9.9):(0.1-1), including but not limited to 9.9:0.1, 9.7:0.3, 9.5:0.5, 9.3:0.7 or 9.1:0.9 or 9.0:1.0, etc.

[0084] In some embodiments, the total thickness of all first composite material layers 2 located on the same surface of the current collector 1 is 60-90 μm, including but not limited to 60 μm, 70 μm, 80 μm or 90 μm.

[0085] It should be noted that in the embodiments of this application, the thickness of each first composite material layer may be the same or different.

[0086] It should also be noted that when multiple surfaces of the current collector are provided with at least two layers of first composite material and second composite material, the multiple first composite material layers on each surface may be the same or different, preferably the same; the multiple second composite material layers on each surface may be the same or different, preferably the same.

[0087] As a preferred example, at least two layers of first composite material 2 and second composite material 3 are sequentially stacked on both opposite surfaces of the current collector 1.

[0088] In some embodiments, the total number of layers of the first composite material layer 2 located on the same surface of the current collector 1 is 2-5 layers, including but not limited to 2, 3, 4 or 5 layers.

[0089] In some embodiments, the thickness of the second composite material layer 3 located on the same surface as the current collector 1 is 3-5 μm, including but not limited to 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0090] In some embodiments, the thickness of the negative electrode sheet is 130-210 μm, including but not limited to 130 μm, 150 μm, 170 μm, 190 μm or 210 μm.

[0091] In the embodiments of this application, the thickness of the negative electrode sheet includes the thickness of the current collector 1 and the thickness of the first composite material layer 2 and the second composite material layer 3 on all surfaces of the current collector 1.

[0092] In some embodiments, the areal density of the first composite material layer 2 to the areal density of the second composite material layer 1 is (9-9.9):(0.1-1), including but not limited to 9.9:0.1, 9.7:0.3, 9.5:0.5, 9.3:0.7, or 9.1:0.9 or 9.0:1.0, etc.

[0093] In some implementations, such as Figure 2 As shown, there are two first composite material layers on the same surface of the current collector 1. The material adjacent to the first composite material layer 1 (labeled as first composite material layer A 201 for ease of description) contains alloy-type negative electrode material and first conductive agent with mass contents of a% and b%, respectively. The material adjacent to the second composite material layer 3 (labeled as first composite material layer B 202 for ease of description) contains alloy-type negative electrode material and first conductive agent with mass contents of c% and d%, respectively. c, d, a, and b satisfy:

[0094] 20% ≤ c / (a+c) < 50%, and / or 20% ≤ d / (b+d) < 50%.

[0095] In the embodiments of this application, when the number of first composite material layers is two, the mass content a% of alloy-type negative electrode material in the first composite material layer A 201 and the mass content c% of alloy-type negative electrode material in the first composite material layer B 202 conform to the above-mentioned relationship of 20% ≦ c / (a+c) < 50%. This can solve the problem that when the proportions of alloy-type negative electrode material and hard carbon-type first carbon material negative electrode are the same in the upper and lower layers (i.e., the first composite material layer A 201), the sodium embedding depth in the upper layer (i.e., the first composite material layer B 202) is too large, which leads to the electrode sheet being prone to pulverization. When the alloy anode content of the first composite material layer B 202 is less than 20% (i.e., the value of c / (a+c) is less than 20%), the content of the upper layer (i.e., the first composite material layer B 202) alloy anode material is too low, and the upper layer alloy anode material has enough first carbon material to buffer it. However, the corresponding content of the alloy anode material in the first composite material layer A 201 (close to the current collector layer) will be too high, and the content of first carbon material will be insufficient to buffer the expansion of the alloy anode material, resulting in cracking of the electrode from the inside out. Similarly, when the alloy anode content of the first composite material layer B 202 is above 50% (i.e., the value of c / (a+c) is greater than or equal to 50%), the content of the upper layer (i.e., the first composite material layer B 202) alloy anode material is too high, and the upper layer alloy anode material does not have enough first carbon material to buffer the expansion of the alloy anode material, also resulting in cracking of the electrode from the inside out.

[0096] The mass content b% of the first conductive agent in the first composite material layer A 201 and the mass content d% of the first conductive agent in the first composite material layer B 202 conform to the above-mentioned relationship 20% ≦d / (b+d) < 50%. That is, the content of the first conductive agent in the first composite material layer A near the current collector is higher than the content of the first conductive agent in the first composite material layer B far away from the current collector. This can accelerate the conversion rate of sodium ions and increase the speed of sodium ion insertion and extraction (because as sodium ions migrate into the electrode, the deeper the migration, the greater the difficulty of sodium ion diffusion, and the fewer sodium ions enter the inner layer. If the conductive agent content is insufficient at this time, it will affect the speed of sodium ions gaining and losing electrons. Therefore, it is necessary to ensure that there is conductive agent at more sites so that the sodium ions that migrate to the inner layer will undergo the reaction of gaining and losing electrons more quickly. Therefore, the content of the first conductive agent near the inner side of the current collector should be higher). If the value of d / (b+d) is less than 20%, then the first conductive agent in the first composite material layer B 202 is too small, which will limit the electron migration rate; if the value of d / (b+d) is greater than or equal to 50%, then the content of the first conductive agent in the first composite material layer A 201 is low. At the same time, this layer is closer to the current collector, and the low content of the first conductive agent will further worsen the rate at which sodium ions gain or lose electrons.

[0097] When the values ​​of c / (a+c) and d / (b+d) simultaneously satisfy the above relationships of 20% ≤ c / (a+c) < 50% and 20% ≤ d / (b+d) < 50%, because sodium ions have greater difficulty embedding into the negative electrode sheet from the outside to the inside (closer to the current collector), the surface layer has a higher sodium ion content, resulting in a greater embedding depth into the negative electrode material. In the layered distribution of alloy-type negative electrode materials, the amount of alloy-type negative electrode material is less in the first composite material layer B, which is farther from the current collector, and less in the inner first composite material layer A. The presence of slightly more alloy-type negative electrode material in the inner layer (B 201) can mitigate the expansion and differentiation that can occur when there is a greater amount of alloy-type negative electrode material on the surface layer, resulting in a deeper embedding depth. Layering the alloy material evens out the embedding depth of sodium ions in the negative electrode between the surface and inner layers. Simultaneously, the layered distribution of conductive agent optimizes the rate of electron gain and loss for sodium ions along the entire electrode thickness. The alloy-type negative electrode material closer to the current collector can also gain and lose electrons more quickly, further facilitating a more balanced sodium embedding depth between the upper and lower alloy layers. Furthermore, the reduced amount of alloy-type negative electrode material in the upper layer (i.e., the first composite material layer B 202) mitigates the sodium embedding depth, providing protection by covering cracks caused by the expansion of the alloy-type negative electrode material near the current collector, and further preventing side reactions between the electrolyte and the fresh alloy-type negative electrode material.

[0098] It should be noted that, in the embodiments of this application, the sum of the mass content of each component (first carbon material, first conductive agent, alloy-type negative electrode material, etc. (e.g., if there is a first binder, it also includes the first binder)) in each first composite material layer material is 100%, and the sum of the mass content of each component (second carbon material, second conductive agent, etc. (if there is a second binder, it also includes the second binder)) in the second composite material layer material is 100%.

[0099] As a more preferred example, such as Figure 2 As shown, two layers of first composite material and two layers of second composite material 3 are sequentially stacked on both opposite surfaces of the current collector 1. As described above, the first composite material layer adjacent to the current collector 1 is marked as first composite material layer A 201, and the first composite material layer adjacent to the second composite material layer 3 is marked as first composite material layer B 202.

[0100] For example, when the negative electrode is as follows Figure 2 When the first composite material layer shown is a two-layer negative electrode sheet, the materials of the first composite material layer A 201 and the first composite material layer B 202 both include a first carbon material, an alloy-type negative electrode material, a first conductive agent, and a first binder. The materials of the second composite material layer 3 include a second carbon material, a second conductive agent, and a second binder.

[0101] The negative electrode sheet of this application embodiment can bring at least the following technical effects:

[0102] Multiple first composite material layers and second composite material layers are sequentially stacked on at least one surface of the current collector. The materials of all first composite material layers include a first carbon material, an alloy-type negative electrode material, and a first conductive agent. The mass content of the alloy-type negative electrode material and the first conductive agent in the materials of the multiple first composite material layers located on the same surface of the current collector decreases sequentially from the side closer to the current collector to the side farther away from the current collector. This increases the migration speed of sodium ions and other substances in the negative electrode sheet near the current collector and reduces the difference in the degree of sodium embedding of the alloy-type negative electrode material on the side farther away from the current collector and the side closer to the current collector (that is, it optimizes the sodium embedding depth of the alloy-type negative electrode material on the side farther away from the current collector and the side closer to the current collector). This alleviates the problem of electrode sheet shattering caused by excessive sodium embedding depth of the alloy-type negative electrode material on the side farther away from the current collector and ensures the stability of the negative electrode sheet. In addition, a second composite material layer containing a second carbon material is set on the surface to restrain the expansion of the negative electrode sheet.

[0103] <Preparation method of negative electrode>

[0104] The method for preparing the negative electrode sheet according to the embodiments of this application can be used to prepare the negative electrode sheet according to the embodiments of this application.

[0105] The method for preparing the negative electrode sheet according to the embodiments of this application includes the following steps:

[0106] S101. Prepare the first composite material layer slurry and the second composite material layer slurry respectively.

[0107] As an optional example, each first composite material layer slurry is composed of the first carbon material, the alloy-type negative electrode material, the first conductive agent, and the first binder. During preparation, the first carbon material, the alloy-type negative electrode material, the first conductive agent, and the first binder of each first composite material layer are mixed according to their respective ratios, and then added to deionized water for uniform mixing to obtain the slurry of the corresponding first composite material layer.

[0108] As an optional example, the second composite material layer slurry is composed of the second carbon material, the second conductive agent, and the second binder; during preparation, the second carbon material, the second conductive agent, and the second binder are mixed, and then added to deionized water for uniform mixing to obtain the slurry of the second composite material layer.

[0109] It should be noted that the selection of materials for the first carbon material, the alloy-type negative electrode material, the first conductive agent, the first binder, the second carbon material, the second conductive agent, and the second binder is the same as that in the negative electrode sheet of this embodiment, and will not be repeated here.

[0110] S102. Using the first composite material layer slurry and the second composite material layer slurry as raw materials, the first composite material layer and the second composite material layer are sequentially formed on the surface of the current collector by a layered coating method.

[0111] Secondary batteries

[0112] The secondary battery of this application embodiment includes a positive electrode, a separator, and a negative electrode, wherein the negative electrode is the negative electrode of this application embodiment.

[0113] In some embodiments, the secondary battery includes, but is not limited to, sodium-ion batteries, with sodium-ion batteries being preferred.

[0114] The method for preparing the negative electrode sheet and the secondary battery of the present application embodiments both have at least the beneficial effects of the negative electrode sheet of the present application embodiments.

[0115] The following non-limiting embodiments further illustrate certain features of the present technology.

[0116] I. Examples and Comparative Examples

[0117] Example 1

[0118] (Negative electrode plate)

[0119] like Figure 2 As shown, the negative electrode sheet of this embodiment includes a current collector 1. The current collector 1 has a first surface 201 and a second surface 202 disposed opposite to each other. A first composite material layer A201, a first composite material layer B202, and a second composite material layer 3 are sequentially stacked on both the first surface 201 and the second surface 202. The first composite material layer A201 on the first surface 101 is exactly the same as the first composite material layer A201 on the second surface 102, the first composite material layer B202 on the first surface 101 is exactly the same as the first composite material layer B202 on the second surface 102, and the second composite material layer 3 on the first surface 101 is exactly the same as the second composite material layer 3 on the second surface 102. Specifically:

[0120] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 90.9%, Sb 4.0%, conductive carbon black (SP) 1.6%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0121] The materials of the first composite layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 95.1%, Sb 1.0%, conductive carbon black (SP) 0.4%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0122] The materials of the second composite material layer 3 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 94.5%, conductive carbon black (SP) 2%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0123] The mass ratio of the materials of the first composite material layer A 201, the first composite material layer B 202, and the second composite material layer 3 on the first surface 201 and the second surface 202 is 7.84:1.96:0.2; the hard carbon is all biomass-derived hard carbon material; the thickness of the first composite material layer A 201 on the first surface 201 and the second surface 202 is 67 μm (single-sided thickness), the thickness of the first composite material layer B 202 on the first surface 201 and the second surface 202 is 17 μm (single-sided thickness), and the thickness of the second composite material layer 3 on the first surface 201 and the second surface 202 is 1.7 μm (single-sided thickness); the negative electrode current collector is an aluminum foil with a thickness of 13 μm, and the thickness of the negative electrode sheet is 184.4 μm (double-sided thickness 67*2+17*2+1.7*2+13); the first composite material layer A 201 and the first composite material layer B 202 on the first surface 201 and the second surface 202 are... The areal density ratio of 202 is 8:2, and the areal density of the first composite material layer A 201 on the first surface 201 and the second surface 202 is 128 g / m³. 2 (Double-sided surface density), the surface density of the first composite material layer B 202 on the first surface 201 and the second surface 202 is 32 g / m². 2 (Double-sided areal density), the areal density of the second composite material layer on both the first surface 201 and the second surface 202 is 3.0 g / m³. 2 (Double-sided areal density); the areal density of the negative electrode is 163.2 g / m². 2 (Double-sided surface density).

[0124] (Preparation method of negative electrode sheet)

[0125] The method for preparing the negative electrode sheet in this embodiment includes the following steps:

[0126] (1) Preparation of the first composite material layer A slurry: Hard carbon, Sb, SP, CMC and SBR are mixed according to the proportion of each component of the first composite material layer A 201 in the negative electrode sheet of this embodiment, and then added to deionized water and mixed evenly to obtain the first composite material layer A slurry.

[0127] (2) Preparation of the first composite material layer B slurry: Hard carbon, Sb, SP, CMC and SBR are mixed according to the proportion of each component of the first composite material layer B 202 in the negative electrode sheet of this embodiment, and then added to deionized water and mixed evenly to obtain the first composite material layer B slurry.

[0128] (3) Preparation of the second composite material layer slurry: Hard carbon, SP, CMC and SBR are mixed according to the proportion of each component of the second composite material layer 3 in the negative electrode sheet of this embodiment, and then added to deionized water and mixed evenly to obtain the second composite material layer slurry.

[0129] (4) Layered coating: This includes the following steps:

[0130] 1) First, the first composite material layer A slurry is coated onto the first surface 101 and the second surface 102 of the current collector, so that the coating surface density is 128 g / m². 2 After drying, a current collector containing the first composite material layer A is obtained;

[0131] 2) Then, in the current collector containing the first composite material layer A, the surface of the first composite material layer A away from the current collector is coated with the first composite material layer B slurry, so that the coating surface density is 32 g / m³. 2 After drying, a current collector containing the first composite material layers A and B is obtained;

[0132] 3) Finally, in the current collector containing the first composite material layers A and B, the surface of the first composite material layer B away from the current collector is coated with the second composite material layer slurry, resulting in a coating surface density of 3 g / m². 2 After baking, the negative electrode sheet of this embodiment is obtained.

[0133] Example 2

[0134] This embodiment is basically the same as embodiment 1, except that:

[0135] In the negative electrode plate:

[0136] The materials of the first composite layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 91.6%, Sb 3.5%, conductive carbon black (SP) 1.4%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0137] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 94.4%, Sb 1.5%, conductive carbon black (SP) 0.6%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0138] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 7:3, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 112 g / m³. 2 .

[0139] In the preparation method of the negative electrode sheet:

[0140] In step (4) layer coating step 1), the coating surface density is made to be 112 g / m². 2 ;

[0141] In step (4), during the layered coating process in step 2), the coating surface density is made to be 48 g / m². 2 .

[0142] Example 3

[0143] This embodiment is basically the same as embodiment 1, except that:

[0144] In the negative electrode plate:

[0145] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 92.3%, Sb 3.0%, conductive carbon black (SP) 1.2%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0146] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 93.7%, Sb 2.0%, conductive carbon black (SP) 0.8%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0147] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 6:4, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 96 g / m³. 2 .

[0148] In the preparation method of the negative electrode sheet:

[0149] In step (4) of layered coating step 1), the coating surface density is made to be 96 g / m². 2 ;

[0150] In step (4), during the layered coating process in step 2), the coating surface density is made to be 64 g / m². 2 .

[0151] Example 4

[0152] This embodiment is basically the same as embodiment 1, except that:

[0153] In the negative electrode plate:

[0154] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 92.86%, Sb 2.6%, conductive carbon black (SP) 1.04%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0155] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 93.14%, Sb 2.4%, conductive carbon black (SP) 0.96%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0156] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 52:48, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 83.2 g / m³. 2 .

[0157] In the preparation method of the negative electrode sheet:

[0158] In step (4), the layered coating process in step 1) achieves a coating surface density of 83.2 g / m². 2 ;

[0159] In step (4), during the layered coating process in step 2), the surface density of the coating is made to be 76.8 g / m². 2 .

[0160] Example 5

[0161] This embodiment is basically the same as embodiment 1, except that:

[0162] In the negative electrode plate:

[0163] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 91.3%, Sb 4.0%, conductive carbon black (SP) 1.2%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0164] The materials of the first composite layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 94.7%, Sb 1.0%, conductive carbon black (SP) 0.8%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0165] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 8:2, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 128 g / m³. 2 .

[0166] In the preparation method of the negative electrode sheet:

[0167] In step (4) layer coating, the coating surface density is made to be 128 g / m². 2 ;

[0168] In step (4), during the layered coating process in step 2), the coating surface density is made to be 32 g / m². 2 .

[0169] Example 6

[0170] This embodiment is basically the same as embodiment 1, except that:

[0171] In the negative electrode plate:

[0172] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 91.9%, Sb 3.0%, conductive carbon black (SP) 1.6%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0173] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 94.1%, Sb 2.0%, conductive carbon black (SP) 0.4%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0174] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 6:4, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 96 g / m³. 2 .

[0175] In the preparation method of the negative electrode sheet:

[0176] In step (4) of layered coating step 1), the coating surface density is made to be 96 g / m². 2 ;

[0177] In step (4), during the layered coating process in step 2), the coating surface density is made to be 64 g / m². 2 .

[0178] Example 7

[0179] This embodiment is basically the same as embodiment 1, except that:

[0180] In the negative electrode plate:

[0181] The materials of the first composite layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 49.5%, Sb 49.5%, conductive carbon black (SP) 0.5%, carboxymethyl cellulose (CMC) 0.25%, and styrene-butadiene rubber (SBR) 0.25%.

[0182] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: 87% hard carbon, 12.375% Sb, 0.125% conductive carbon black (SP), 0.25% carboxymethyl cellulose (CMC), and 0.25% styrene-butadiene rubber (SBR).

[0183] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 3:7, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 48 g / m³. 2 .

[0184] In the preparation method of the negative electrode sheet:

[0185] In step (4), the layered coating process in step 1) achieves a coating surface density of 48 g / m². 2 ;

[0186] In step (4) of layered coating step (2), the coating surface density is made to be 112 g / m². 2 .

[0187] Example 8

[0188] This embodiment is basically the same as embodiment 1, except that:

[0189] In the negative electrode plate:

[0190] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 94.5%, Sb 0.4%, conductive carbon black (SP) 1.6%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0191] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: 96% hard carbon, 0.1% Sb, 0.4% conductive carbon black (SP), 1.5% carboxymethyl cellulose (CMC), and 2.0% styrene-butadiene rubber (SBR).

[0192] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 52:48, and the areal density of the first composite material layer A 201 is 83.2 g / m³. 2 .

[0193] In the preparation method of the negative electrode sheet:

[0194] In step (4), the layered coating process in step 1) achieves a coating surface density of 83.2 g / m². 2 ;

[0195] In step (4), during the layered coating process in step 2), the surface density of the coating is made to be 76.8 g / m². 2 .

[0196] Example 9

[0197] This embodiment is basically the same as embodiment 1, except that:

[0198] In the negative electrode plate:

[0199] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 6:4, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 96 g / m³. 2 .

[0200] In the preparation method of the negative electrode sheet:

[0201] In step (4) of layered coating step 1), the coating surface density is made to be 96 g / m². 2 ;

[0202] In step (4), during the layered coating process in step 2), the coating surface density is made to be 64 g / m². 2 .

[0203] Example 10

[0204] This embodiment is basically the same as embodiment 1, except that:

[0205] In the negative electrode plate:

[0206] A first composite material layer C is added between the first composite material layer B 202 and the second composite material layer 3 on the first surface 201 and the second surface 202; the first composite material layer C on the first surface 101 is exactly the same as the first composite material layer C on the second surface 102.

[0207] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: 69% hard carbon, 25% Sb, 2.5% conductive carbon black (SP), 1.5% carboxymethyl cellulose (CMC), and 2.0% styrene-butadiene rubber (SBR).

[0208] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: 80% hard carbon, 15% Sb, 1.5% conductive carbon black (SP), 1.5% carboxymethyl cellulose (CMC), and 2.0% styrene-butadiene rubber (SBR).

[0209] The materials of the first composite layer C on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: 86% hard carbon, 10% Sb, 0.5% conductive carbon black (SP), 1.5% carboxymethyl cellulose (CMC), and 2.0% styrene-butadiene rubber (SBR).

[0210] The mass ratio of the first composite material layer A 201, the first composite material layer B 202, the first composite material layer C, and the second composite material layer 3 on the first surface 201 and the second surface 202 is 80:48:32:3; the thickness of the first composite material layer A 201 on the first surface 201 and the second surface 202 is 42.0 μm, the thickness of the first composite material layer B 202 on the first surface 201 and the second surface 202 is 26.0 μm, the thickness of the first composite material layer C on the first surface 201 and the second surface 202 is 17.0 μm, the thickness of the second composite material layer 3 on the first surface 201 and the second surface 202 is 1.6 μm, and the thickness of the negative electrode sheet is 186.2 μm (42*2+26*2+17*2+1.6*2+13); the mass ratio of the first composite material layer A 201, the first composite material layer B 202, the first composite material layer C, and the second composite material layer 3 on the first surface 201 and the second surface 202 is 80:48:32:3; 202. The areal density ratio of the first composite material layer C is 80:48:32, and the areal density of the first composite material layer A 201 on the first surface 201 and the second surface 202 is 80 g / m³. 2 .

[0211] In the preparation method of the negative electrode sheet:

[0212] It also includes: preparation of the first composite material layer C slurry: hard carbon, Sb, SP, CMC and SBR are mixed according to the proportion of each component of the first composite material layer C in the negative electrode sheet of this embodiment, and then added to deionized water and mixed evenly to obtain the first composite material layer C slurry.

[0213] Step (4) Layered coating: This includes the following steps:

[0214] 1) First, the first composite material layer A slurry is coated onto the first surface 101 and the second surface 102 of the current collector, so that the coating surface density is 80 g / m². 2 After drying, a current collector containing the first composite material layer A is obtained;

[0215] 2) Then, in the current collector containing the first composite material layer A, the surface of the first composite material layer A away from the current collector is coated with the first composite material layer B slurry, so that the coating surface density is 48 g / m³. 2 After drying, a current collector containing the first composite material layers A and B is obtained;

[0216] 3) Then, in the current collector containing the first composite material layers A and B, the surface of the first composite material layer B away from the current collector is coated with the first composite material layer C slurry, so that the coating surface density is 32 g / m³. 2 After drying, a current collector containing the first composite material layers A, B, and C is obtained;

[0217] 4) Finally, in the current collector containing the first composite material layers A, B, and C, the surface of the first composite material layer C away from the current collector is coated with the second composite material layer slurry, resulting in a coating surface density of 3 g / m³. 2 The discharge capacity is 300mAh / g, and then it is baked to obtain the negative electrode sheet of this embodiment.

[0218] Example 11

[0219] This embodiment is basically the same as embodiment 1, except that:

[0220] All Sb was replaced with a silicon-germanium alloy in which the mass ratio of silicon to germanium was 5:5.

[0221] Example 12

[0222] This embodiment is basically the same as embodiment 1, except that:

[0223] In the negative electrode plate:

[0224] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 89.9%, Sb 1.6%, conductive carbon black (SP) 5%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0225] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 94.85%, Sb 0.4%, conductive carbon black (SP) 1.25%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0226] The areal density ratio of the first composite material layer A 201 to the first composite material layer B 202 on both the first surface 201 and the second surface 202 is 8:2, and the areal density of the first composite material layer A 201 on both the first surface 201 and the second surface 202 is 128 g / m³. 2 .

[0227] In the preparation method of the negative electrode sheet:

[0228] In step (4) layer coating, the coating surface density is made to be 128 g / m². 2 ;

[0229] In step (4), during the layered coating process in step 2), the coating surface density is made to be 32 g / m². 2 .

[0230] Example 13

[0231] This embodiment is basically the same as embodiment 1, except that:

[0232] All hard carbon in all first composite material layers A 201, all first composite material layers B 202 and all second composite material layers 3 are replaced with soft carbon, and all conductive carbon black (SP) is replaced with carbon nanotubes.

[0233] Comparative Example 1

[0234] The negative electrode sheet in this comparative example includes a current collector, which has surfaces A and B arranged opposite to each other. Both surfaces A and B are provided with a composite material layer. Wherein:

[0235] The composite material layers on surfaces A and B are composed of the following components by mass percentage: 89.5% hard carbon, 5% Sb, 2% conductive carbon black (SP), 1.5% carboxymethyl cellulose (CMC), and 2.0% styrene-butadiene rubber (SBR).

[0236] The total mass of the composite material layers on surface A is the same as the total mass of the first composite material layer A201, the first composite material layer B202, and the second composite material layer 3 on the first surface 101 in Example 1; the total mass of the composite material layers on surface B is the same as the total mass of the first composite material layer A201, the first composite material layer B202, and the second composite material layer 3 on the first surface 102 in Example 1; the hard carbon is all biomass-derived hard carbon material, the thickness of the composite material layers on both surface A and surface B is 86 μm (the total thickness of the composite material layers on both surface A and surface B is 172 μm), the negative electrode current collector is an aluminum foil with a thickness of 13 μm, and the thickness of the negative electrode sheet is 185 μm; the areal density of the composite material layers on both surface A and surface B is 163.2 g / m³. 2 .

[0237] The negative electrode sheet of this comparative example is prepared as follows: Hard carbon, Sb, SP, CMC, and SBR are mixed in the specified amounts, then added to deionized water and mixed thoroughly to obtain a composite material slurry. The composite material slurry is then coated onto one surface of the current collector, resulting in a coating surface density of 163.2 g / m². 2 The discharge capacity was 310mAh / g, and then it was baked to obtain the negative electrode sheet of this comparative example.

[0238] Comparative Example 2

[0239] This comparative example is basically the same as Example 1, except that:

[0240] In the negative electrode sheet, neither the first surface 201 nor the second surface 202 contains the second composite material layer 3.

[0241] In the preparation method of the negative electrode sheet:

[0242] Step 3 in steps (3) and (4) is excluded.

[0243] Comparative Example 3

[0244] This comparative example is basically the same as Example 1, except that:

[0245] In the negative electrode plate:

[0246] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 95.1%, Sb 1.0%, conductive carbon black (SP) 0.4%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0247] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 80.9%, Sb 4.0%, conductive carbon black (SP) 1.6%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0248] Comparative Example 4

[0249] This comparative example is basically the same as Example 1, except that:

[0250] In the negative electrode plate:

[0251] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 93.9%, Sb 1.0%, conductive carbon black (SP) 1.6%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0252] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 92.1%, Sb 4.0%, conductive carbon black (SP) 0.4%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0253] Comparative Example 5

[0254] This comparative example is basically the same as Example 1, except that:

[0255] In the negative electrode plate:

[0256] The materials of the first composite material layer A 201 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 93.9%, Sb 4.0%, conductive carbon black (SP) 0.4%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0257] The materials of the first composite material layer B 202 on the first surface 201 and the second surface 202 are both composed of the following components in mass percentage: hard carbon 92.1%, Sb 1.0%, conductive carbon black (SP) 1.6%, carboxymethyl cellulose (CMC) 1.5%, and styrene-butadiene rubber (SBR) 2.0%.

[0258] II. Performance Testing

[0259] The negative electrode sheets from each embodiment or comparative example were assembled into sodium-ion batteries, and the electrochemical performance of the assembled sodium-ion batteries was tested. Among them:

[0260] The assembly method of a sodium-ion battery includes the following steps:

[0261] (1) Preparation of positive electrode sheet: layered oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, polyvinylidene fluoride (PVDF) binder, and carbon black conductive agent are mixed at a fixed mass ratio of 96%, 2%, and 2%, respectively. Then, N-methylpyrrolidone solvent is added and stirred to prepare a positive electrode slurry. The positive electrode slurry is then uniformly coated onto the opposite surfaces of a 13μm thick aluminum foil, with a coating density of 350 g / m². 2 After coating, the positive electrode sheet is baked, then cold-pressed, trimmed, cut, and slit, and then the tabs are welded to obtain a spare positive electrode sheet.

[0262] (2) After cold pressing, trimming, cutting and slitting the negative electrode sheets of each embodiment or comparative example, the electrode tabs are welded to obtain spare negative electrode sheets.

[0263] (3) Electrolyte preparation: First, in a glove box, sodium salt was added to a mixture of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1:1. After mixing evenly, the electrolyte was prepared. The sodium salt concentration was 1.2 mol / L.

[0264] (4) Battery assembly: The above-mentioned spare positive electrode, spare negative electrode and separator (polyethylene (PE) base film + single-sided ceramic, PE base film thickness 9μm, ceramic thickness 2μm) are stacked to form a bare cell, which is then placed in an aluminum-plastic film; then vacuum baked at 95°C to remove moisture, and then injected with electrolyte and sealed; after standing, formation, degassing, sealing and capacity testing, a sodium-ion battery is obtained.

[0265] Electrochemical performance testing:

[0266] The test method for the full-charge negative electrode expansion rate is as follows: First, fully charge the battery according to the following steps; the full-charge process is 1C constant current and constant voltage charging, with an upper limit voltage of 3.95V and a cutoff current of 0.05C; then disassemble the battery, separate the negative electrode sheet, and test the thickness of the negative electrode sheet, recording it as d1. The thickness of the negative electrode sheet after rolling in each embodiment and comparative example is d0; the thickness of the current collector of the negative electrode sheet is recorded as d; the full-charge expansion rate of the negative electrode sheet η1=(d1-d0) / (d0-d).

[0267] The test method for capacity retention after 500 cycles is as follows: Empty the battery completely, then charge and discharge it according to the following procedure. Each complete charge-discharge cycle is recorded as one cycle; the capacity of the first cycle is taken as the initial capacity C1, and the capacity of the 500th cycle is taken as C... 500 Capacity retention rate η2 = C after 500 cycles 500 / C1; where,

[0268] Battery depletion procedure: Discharge at 1C constant current to the lower limit voltage of 1.5V;

[0269] Charge / discharge process: 1C constant current and constant voltage charging, upper limit voltage 3.95V, cutoff current 0.05C; rest for 10min; 1C constant current discharging to lower limit voltage 1.5V; rest for 10min.

[0270] The test method for the increase in internal resistance after 500 cycles is as follows: Using a conventional voltage internal resistance tester, the AC internal resistance of the battery in the first cycle is recorded as R1; the AC internal resistance of the battery in the 500th cycle is recorded as R. 500 The internal resistance of a battery increases by η3 = R after 500 cycles. 500 / R1.

[0271] The electrochemical performance test results of the sodium-ion batteries corresponding to the negative electrode sheets of each embodiment and comparative example are shown in Table 1.

[0272] Table 1 Electrochemical performance test results

[0273]

[0274]

[0275] According to Table 1:

[0276] Comparing Examples 1-13 and Comparative Example 1, it can be seen that the solution of the present application embodiment has significant improvements in the negative electrode plate full charge rebound, battery cycle life, and the proportion of increase in battery impedance after cycling.

[0277] Comparing Example 1 and Comparative Example 2, it can be seen that when the second composite material layer is not present, the expansion rate of the fully charged negative electrode and the increase in internal resistance after 500 cycles both increase significantly, while the capacity retention rate after 500 cycles decreases.

[0278] Comparing Example 1 and Comparative Examples 3-5, it can be seen that when the content of alloy-type negative electrode material and first conductive agent in the first composite material layer A 201 and the first composite material layer B 202 does not conform to the rules of this application, the expansion rate of the fully charged negative electrode and the increase ratio of internal resistance after 500 cycles both increase significantly, while the capacity retention rate after 500 cycles decreases significantly.

[0279] In summary, the negative electrode sheet and its preparation method of this application improve the problem of large expansion of the negative electrode after sodium intercalation in sodium-ion batteries, where the first carbon material such as hard carbon and alloy negative electrode material are mixed. By layering coating, the proportion of alloy negative electrode material and first conductive agent in the first composite material layer material on the side away from the current collector and the side close to the current collector is optimized, and the sodium intercalation depth of the alloyed negative electrode on the side away from the current collector and the side close to the current collector is optimized, thus alleviating the problem of electrode sheet crushing caused by excessive sodium intercalation depth on the surface.

[0280] In this application, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0281] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0282] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A negative electrode sheet, characterized in that, The current collector includes a current collector, wherein at least one surface of the current collector is provided with at least two layers of first composite material and second composite material in sequence; All the materials of the first composite material layer include a first carbon material, an alloy-type negative electrode material, and a first conductive agent; among the materials of any two adjacent first composite material layers located on the same surface of the current collector, the mass content of the alloy-type negative electrode material in the material of the first composite material layer closer to the current collector is greater than the mass content of the alloy-type negative electrode material in the material of the first composite material layer closer to the second composite material layer, and the mass content of the first conductive agent in the material of the first composite material layer closer to the current collector is greater than the mass content of the first conductive agent in the material of the first composite material layer closer to the second composite material layer. The material of the second composite material layer includes a second carbon material and a second conductive agent; The mass content of the first carbon material in the first composite material layer is less than or equal to the mass content of the second carbon material in the second composite material layer; The first carbon material includes at least one of hard carbon and soft carbon; The alloy-type negative electrode material includes at least one of antimony, tin, phosphorus, silicon, bismuth, and germanium; The mass content of the first carbon material in the first composite material layer is greater than or equal to the mass content of the alloy-type anode material; In the material of the first composite material layer adjacent to the current collector, the mass content of the first conductive agent is b%; In the material of the first composite material layer adjacent to the second composite material layer, the mass content of the first conductive agent is d%; where d and b satisfy: 20%≦d / (b+d)<50%.

2. The negative electrode sheet according to claim 1, characterized in that, The second carbon material includes at least one of hard carbon and soft carbon; And / or, the first conductive agent and the second conductive agent include at least one of conductive carbon black, superconducting carbon, conductive graphite, carbon nanotubes, and graphene.

3. The negative electrode sheet according to claim 1, characterized in that, The total mass content of the alloy-type negative electrode material in the negative electrode sheet is greater than 0% and less than 49.5%; And / or, in the material of the first composite material layer, the mass content of the first conductive agent is 0.4-5.0%; And / or, in the material of the second composite layer, the mass content of the second conductive agent is 0.5-5.0%.

4. The negative electrode sheet according to claim 3, characterized in that, The mass content of the first carbon material in the first composite material layer is 49.5-99%; And / or, when the number of layers in the first composite material layer is two, the mass content of the alloy-type negative electrode material in the first composite material layer is m, 0 < m ≤ 49.5%; or, when the number of layers in the first composite material layer is greater than two, the mass content of the alloy-type negative electrode material in the first composite material layer is n, 0 ≤ n ≤ 49.5%; And / or, the mass content of the second carbon material in the second composite material layer is 90-99%.

5. The negative electrode sheet according to claim 1, characterized in that, All materials of the first composite material layer also include a first adhesive; And / or, the material of the second composite layer further includes a second adhesive.

6. The negative electrode sheet according to claim 5, characterized in that, In the material of the first composite layer, the mass content of the first adhesive is 0.5-5.0%; And / or, in the material of the second composite layer, the mass content of the second adhesive is 0.5-5.0%; And / or, both the first adhesive and the second adhesive comprise at least one of styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.

7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that, The number of the first composite material layers located on the same surface of the current collector is two, and, In the material of the first composite material layer adjacent to the current collector, the mass content of the alloy-type negative electrode material is a% In the material of the first composite material layer adjacent to the second composite material layer, the mass content of the alloy-type negative electrode material is c%; where c and a satisfy: 20%≦c / (a+c)<50%.

8. The negative electrode sheet according to claim 1, characterized in that, The two opposing surfaces of the current collector are each provided with at least two layers of first composite material and second composite material in sequence; And / or, the total thickness of all the first composite material layers located on the same surface of the current collector is 60-90 μm; And / or, the total number of the first composite material layers located on the same surface of the current collector is 2-5 layers; And / or, the thickness of the second composite material layer located on the same surface of the current collector is 1-5 μm; And / or, the thickness of the negative electrode sheet is 130-210 μm; And / or, the ratio of the areal density of the first composite material layer to the areal density of the second composite material layer is (9-9.9):(0.1-1).

9. A method for preparing a negative electrode sheet as described in any one of claims 1 to 8, characterized in that, include: Prepare the first composite material layer slurry and the second composite material layer slurry respectively; Using the first composite material layer slurry and the second composite material layer slurry as raw materials, the first composite material layer and the second composite material layer are sequentially formed on at least one surface of the current collector by a layered coating method.

10. A secondary battery, comprising a positive electrode, a separator, and a negative electrode, characterized in that, The negative electrode is the negative electrode as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Negative pole piece, secondary battery, battery module, battery pack and electric device

    CN116034497A

  • Low-expansion silicon-carbon negative electrode and lithium ion battery thereof

    CN217641407U